The Impact of the Coronavirus (COVID-19) Infection on the Drug- Metabolizing Enzymes Cytochrome P450s - Elfaki, Imadeldin (Drug Metabolism and Bioanalysis Letters, 2022)
Coronaviruses cause disease in humans and animals. In 2019 a novel coronavirus was first characterized in Wuhan, China causing acute respiratory disease and designating the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) or COVID-19. The COVID-19 spread to all cities of China and in 2020 to the whole world. Patients with COVID-19 may recover without medical treatment. However, some patients need medical care. The Cytochrome p450s (CYP450s) are a large superfamily of enzymes that catalyze the metabolism of endogenous substrates and xenobiotics. CYP450s catalyze the biotransformation of 80% of the drug in clinical use. The CYP450 is present in liver, lungs, intestine and other tissues. COVID-19 has been reported to decrease the activity of certain isoforms of CYP450s in an isoform specific manner. Furthermore, the COVID-19 infection decreases the liver functions including the drug clearance or detoxification medicated by the CYP450s. The healthcare providers should be aware of this disease-drug interaction when prescribing drugs for the treatment of COVID-19 and other comorbidities.
Keywords: coronaviruses